Regulation of the brain lipidome in health and disease - Giles, Corey Steven (Curtin University, 2017)
This thesis explores the plasma-brain axis in ‘Regulation of the brain lipidome in health and disease’. Using a comprehensive lipidomics platform, the main experimental objectives of this thesis were to investigate the plasma lipidome as a regulator of the cerebral lipidome. Secondary objectives were to explore the potential for therapeutic modulation of sphingolipid metabolism. The experimental findings provide novel insight into regulatory mechanisms, which are informative in the context of neurodegenerative disease processes.